Analisis Faktor Penyebab Kurangnya Kesadaran Terhadap Tangung Jawab yang Diemban Dalam Organisasi IPNU IPPNU Desa Pepe - Muhammad Ishaqul Hisyam; Wahyu Eko Pujianto (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2024)
The activeness of members in the organization has a huge impact on the continuity of the organization. Work programs and other activities will be hampered if members of the organization are passive in their implementation. This is due to several factors, namely lack of interest, lack of understanding of roles and responsibilities, lack of communication, conflict, and incompatibility between members. The purpose of writing this journal is to find out how to raise awareness about the responsibilities of being a member of IPNU-IPPNU in Pepe Village. This journal uses qualitative methods, personal analysis, and interviews with several members of IPNU-IPPNU Pepe Village. Based on observations that have been made, awareness of responsibility can increase organizational effectiveness, build trust between members, increase job satisfaction, shape character, and improve individual and organizational reputation. To increase this awareness, some steps that can be taken are understanding the responsibilities you have, making plans, prioritizing tasks, not being afraid to ask for help, learning from mistakes